Transformation of Education According to Hadratussyaikh Hasyim Asy'ari An Examination of the Book of Adabul 'Alim wal Muta'alim - Amalia, Ayu; Sopingi, Imam; Hidayati, Athi’; Yumna, Hanin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to examine the idea of educational transformation according to Hadratussyaikh Hasyim Asy'ari as stated in the book Adabul 'Alim wal Muta'alim, as a legacy of classical Islamic thought that is relevant in the modern context. This research uses a qualitative approach with a library research method through hermeneutic text analysis of the contents of the book, and contextualized with contemporary educational issues. The main findings of this study show that Hasyim Asy'ari not only emphasizes ethical aspects in the relationship between teacher and student, but also contains systemic ideas regarding the integration of religious and moral sciences, character building, and the importance of exemplary in educational transformation. These ideas reflect a holistic education model based on spiritual and moral values, which offers a critique of modern education that tends to be secular and instrumental. Thus, Hasyim Asy'ari's thought is a significant contribution in formulating an educational paradigm that is not only oriented to the transfer of knowledge, but also to the formation of the whole person. This finding enriches the treasures of Islamic thought in the field of education and opens space for the development of character education models in the current global context.